2018
DOI: 10.1186/s13063-018-2807-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical ablation versus cyanoacrylate adhesive for the treatment of varicose veins: study protocol for a randomised controlled trial

Abstract: BackgroundThermal ablation techniques have become the first-line treatment of truncal veins in the management of chronic venous disease (CVD). Despite excellent outcomes, these methods are often associated with pain; generally due to their use of heat and the necessity of fluid infiltration around the vein. More recently, novel non-thermal techniques, such as mechanochemical ablation (MOCA) and cyanoacrylate adhesive (CAE) have been developed to overcome these unwelcome effects. So far, the novel techniques ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…MOCCA (MechanOChemical ablation versus Cyanoacrylate Adhesive for the treatment of varicose veins; NCT03392753) is a prospective, multicentre, randomised clinical trial, recruiting patients with truncal saphenous incompetence. 34 Patients will be randomised to undergo either MOCA or CAG truncal ablation, followed by treatment of any varicosities. The primary outcome measure is the pain score immediately following completion of truncal ablation.…”
Section: Discussionmentioning
confidence: 99%
“…MOCCA (MechanOChemical ablation versus Cyanoacrylate Adhesive for the treatment of varicose veins; NCT03392753) is a prospective, multicentre, randomised clinical trial, recruiting patients with truncal saphenous incompetence. 34 Patients will be randomised to undergo either MOCA or CAG truncal ablation, followed by treatment of any varicosities. The primary outcome measure is the pain score immediately following completion of truncal ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the trials and early feasibility studies quote zero percent deep vein thrombosis (DVT) rate and this has been used as a unique selling point to attempt to gain market share, but this is misleading. From the beginning, Almeida's first in man study showed thread-like extension into the common femoral vein [8] and while no PE resulted from this, they have been reported in subsequent series [7,11,24,25]. Less common adverse events of any kind require particular vigilance, and the small numbers in early studies showing no DVT means insufficient power to detect rare but potentially devastating complications.…”
Section: Editorialmentioning
confidence: 99%
“…11,18 Tumescent-less versus tumescent-less Interrogation of four international registries reveals only one trial aiming to compare an endovenous tumescentless method with another. This study, the MOCCA randomised controlled trial 25 (mechanochemical ablation versus cyanoacrylate adhesive in the treatment of truncal saphenous incompetence) was designed to compare the degree of pain that patients experience while receiving MOCA or CAE ablation. So far, the trial has recruited 120 patients of the target 180, and the final results of this trial are expected towards the end of 2020.…”
Section: Tumescent-based Versus Tumescent-lessmentioning
confidence: 99%